The Effectiveness of Using Animated Videos in Learning Mathematics to Improve Student Learning Outcomes in Elementary Schools: A Systematic Literature Review - Ranti Ayu Kartika; Berta Apriza; Darwanto (Indonesian Journal of Educational Research and Review)
Students’ low interest in learning mathematics and their difficulties in understanding abstract concepts remain significant challenges in elementary education. This study aims to analyze the effectiveness of animated videos as a medium for mathematics instruction by employing a Systematic Literature Review (SLR) method. Data were gathered through a structured search of relevant peer-reviewed articles published within the last five years, applying specific inclusion criteria to ensure the quality and relevance of the selected sources. The SLR process was carried out systematically, involving stages of identification, screening, data extraction, and thematic analysis. The findings reveal that animated videos facilitate the delivery of mathematical content in a visual and interactive manner, which enhances students’ conceptual understanding, fosters learning motivation, and improves learning outcomes. This medium proves especially effective in supporting meaningful learning of complex and abstract mathematical topics. The study highlights the importance of content quality, curriculum alignment, and the use of contextually appropriate instructional strategies in maximizing the benefits of animated media. It is concluded that animated videos represent a promising tool for enriching mathematics instruction in elementary classrooms. The study suggests that educators design creative and well-structured animations and encourages future research to further explore technical and pedagogical factors influencing the success of animation-based learning approaches.